The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2174/1875399x010030100118
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Spanish National Team Basketball Players by Age and Sex

Abstract: Abstract:The aim of this study was to analyze the relationship between basketball players that have participated in the Spanish national team at different age categories and their progression through these categories. This progress is differentiated according to sex. The data for this study contain information about 320 players (163 females and 157 males). Results show that only a small percentage of players recognized as talented young players reached athletic excellence when adults. The evolution of the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…7 Attainment of athletic excellence when being adults is limited for a very narrow group of basketball players, independent of gender. 8 In youth basketball, body size and functional performance are important determinants of performance that influence coaches decisions, 4,9 whether to develop and provide training and competition opportunities, or not to promote player’s participation. Often differences in adolescent player’s physique and performance are transient, and may be exacerbated by the complex interaction between pubertal growth rate, chronological age and accumulated sport-specific experience.…”
Section: Introductionmentioning
confidence: 99%
“…7 Attainment of athletic excellence when being adults is limited for a very narrow group of basketball players, independent of gender. 8 In youth basketball, body size and functional performance are important determinants of performance that influence coaches decisions, 4,9 whether to develop and provide training and competition opportunities, or not to promote player’s participation. Often differences in adolescent player’s physique and performance are transient, and may be exacerbated by the complex interaction between pubertal growth rate, chronological age and accumulated sport-specific experience.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Spanish national teams showed the existence of a break in the continuity of participation when comparing U16 and senior categories. 29 This reinforces the notion that as the stages of development progress, the challenges that players must face change whilst the solutions that previously brought success in game scenarios are no longer as effective. For example, the U18 Lithuanian national team performed more 2-point shots, but with lower accuracy, as compared to the U16 national team.…”
Section: Discussionmentioning
confidence: 53%
“…To summarize, when injury history is taken into consideration, basketball players are unlikely to have a significant bilateral lower limb strength imbalance. These findings can be interpreted as reflecting the symmetrical movement patterns of basketball players who use both lower limbs equally during practice and competition [22].…”
Section: Discussionmentioning
confidence: 68%